Examining cultural perspectives in a globalized world - Brunet-Thornton, Richard, 1953- (IGI Global, 2020)
"This book examines the cultural aspects of working across national borders and the cultural challenges faced by international virtual teams. It also explores management dilemmas relative to resource issues when dealing with cultural diversity"--